Airborne a guided tour of an Airborne Task Force - Clancy, Tom (Tom Clancy's military library, 1999)
Representing the very best from the US Army and Air Force, the Airborne Task Force is a formidable combination of manpower and firepower.With Clancy's hallmark pinpoint accuracy and style - more compelling than any fiction - here are the people, the technology and the mission in an ever-changing world of the Airborne juggernaut.Thrillingly, the book includes two Clancy mini-novels - real world scenarios involving the Airborne Task Force - as well as the details of its 21st century weapons (including the Javelin anti-tank missile, the hypersonic LOSAT fire support system and the Comanche Stealth Helicopter), a look at 18 weeks in the life of an Airborne Alert Brigade, and an in-depth interview with the new commander of the 18th Airborne Corps, General John M. Keane.